2019
DOI: 10.3389/fvets.2019.00280
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG—PET/CT in Canine Mammary Gland Tumors

Abstract: Medical imaging techniques play a central role in clinical oncology, helping to obtain important information about the extent of disease, and plan treatment. Advanced imaging modalities such as Positron Emission Tomography–Computed Tomography (PET/CT), may help in the whole-body staging in a single procedure, although the lesions should be carefully interpreted. PET/CT is becoming commonly used in canine cancer patients, but there is still limited information available on specific tumors such as mammary cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…In humans with IMC, an 18 F‐FDG‐PET/CT pattern of multiple scattered highlighted foci, particularly at the site of cutaneous lesions, is observed; this pattern was also observed in this dog (Baslaim et al., 2003). A previous report of 18 F‐FDG PET/CT in dogs with mammary carcinoma recommended a maximum SUV cut‐off for mammary carcinoma of 2 and maximum SUV range for metastatic lymph nodes of 0.56–2.14 (Sánchez et al., 2019). In this dog, the maximum SUV of the right first mammary gland was 3.62, and mammary carcinoma was therefore suspected.…”
Section: Discussionmentioning
confidence: 99%
“…In humans with IMC, an 18 F‐FDG‐PET/CT pattern of multiple scattered highlighted foci, particularly at the site of cutaneous lesions, is observed; this pattern was also observed in this dog (Baslaim et al., 2003). A previous report of 18 F‐FDG PET/CT in dogs with mammary carcinoma recommended a maximum SUV cut‐off for mammary carcinoma of 2 and maximum SUV range for metastatic lymph nodes of 0.56–2.14 (Sánchez et al., 2019). In this dog, the maximum SUV of the right first mammary gland was 3.62, and mammary carcinoma was therefore suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical features, structures or physiological processes can be assessed by employing different imaging methods [ 6 , 7 ]. The main methods used in the imaging of mammary glands of animals include computed tomography, positron emission tomography, magnetic resonance imaging, and ultrasonographic techniques (e.g., B-mode ultrasonography, Doppler ultrasonography, contrast-enchased ultrasonography, three-dimensional ultrasonography, and elastography) [ 2 , 4 , 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…4,9,10 In veterinary medicine, 18 F-FDG-PET/CT has been shown to be an effective staging tool for patients with several different neoplasms, including lymphoma, mast cell tumour, mammary carcinoma, primary lung tumour, histiocytic sarcoma, Sertoli cell tumour and splenic hemangiosarcoma. 7,[11][12][13][14][15] Initial research has also shown that 18 F-FDG-PET/CT is effective for identifying both osseous and soft tissue lesions in dogs afflicted with appendicular osteosarcoma 4 and that the SUV max of the primary lesion is significantly associated with survival time. 10 However, the efficacy of 18 F-FDG-PET/CT has yet to be directly compared to other staging modalities.…”
mentioning
confidence: 99%